(untitled) (Orchid Academia Siraha, 2024)
This case study explores the role and impact of Suryanarayan Satyanarayan Morbaita Yadav Multiple (SSMYM) Campus in promoting higher education in Siraha, Nepal. As a key academic constituent campus of Tribhuvan University, SSMYM Campus serves a diverse student population with programs spanning science, management, education, and humanities. The study highlights the campus’s contributions to social transformation, accessibility to applied education, and regional development. Challenges such as limited infrastructure, faculty shortages, and research gaps are identified. The research emphasizes strategies to address these challenges, including enhanced Tribhuvan University (TU) policies, stakeholder involvement, and curriculum reforms aligned with local and global demands. The findings underscore the need for targeted interventions to strengthen capacity of SSMYM campus to drive educational and socio-economic growth.